Healthy Spending Habits as Drivers of Technopreneurial and Financial Outcomes - Zainol, Zuraidah; Abdul Wahab, Nadratun Nafisah; Shokory, Suzyanty Mohd; Harianto, Prayudi (Aptisi Transactions On Technopreneurship (ATT), 2025)
Healthy spending of the population has been raised as one of the measures to restore social harmony and economic stability. Nevertheless, limited attention has been given to understanding how different forms of spending, rather than saving alone, influence people’s financial conditions and family well-being. This study aims to examine how various spending behaviors including experiential, impulsive, self-expressive, prosocial, and conspicuous spending affect financial well-being and, in turn, marital satisfaction among married individuals in Malaysia. Using a quantitative and deductive research design, data were gathered from 400 married respondents through a structured self-administered questionnaire. The analysis was conducted using Covariance-Based Structural Equation Modeling (CB-SEM) with the aid of AMOS software to validate the hypothesized relationships. The results show that prosocial and conspicuous spending have a significant positive impact on financial well-being, while impulsive spending demonstrates a negative influence. Moreover, financial well-being plays a crucial mediating role, exerting a significant positive effect on marital satisfaction. To enhance both financial stability and relationship satisfaction, individuals should cultivate mindful and responsible spending habits. The findings offer new perspectives for policymakers, businesses, and educators in fostering family harmony and economic empowerment through balanced spending and financial awareness.